Emotional Intelligence with Employability in College Students - Fitriyani, Dewi Annisa; Azis, Abdul (Universitas Negeri Semarang, 2024)
Students need to be equipped with employability, which leads to individual efforts to utilize their knowledge and skills to the fullest to find and maintain employment. One strategy to meet employability standards from companies or recruiters is to increase emotional intelligence. Individuals who have a high level of emotional intelligence will be more confident in displaying their employability. This study aims to determine the relationship between emotional intelligence and employability in students participating in the UNNES PRIGEL MBKM program. The approach used was quantitative correlation and involved 350 students selected through quota sampling. Research data were taken using the employability scale and the Schutte Emotional Intelligence Scale (SEIS). Furthermore, the data were analyzed using Pearson's Product Moment correlation technique. This study obtained the results of the emotional intelligence and employability correlation test, which resulted in a count value = 0.626 with a significance value of p = 0.001 and p < 0.05. These results indicate a relationship between emotional intelligence and employability in college students.